Factors associated with therapy noncompliance in type-2 diabetes patients - Hernández-Ronquillo Lizbeth; Téllez-Zenteno José Francisco; Garduño-Espinosa Juan; González-Acevez Erick (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To identify the frequency and factors associated with therapy noncompliance in type-2 diabetes mellitus patients. MATERIAL AND METHODS: A cross-sectional study was carried out in 79 patients with type-2 diabetes mellitus seen in major hospitals of Mexico City. Patients were visited at home, from March 1998 to August 1999, to measure compliance with prescribed therapy. Complying patients were defined as those taking at least 80% of their pills or 80% of their corresponding insulin dose. The degree of compliance with therapy components (diet, amount of exercise, and keeping appointments) was measured. RESULTS: The average age of study subjects was 59 years (SD 11 years); 73% (n=58) were female subjects. The overall frequency of noncompliance was 39%. Noncompliance rates were: 62% for dietary recommendations, 85% for exercise, 17% for intake of oral hypoglycemic medication, 13% for insulin application, and 3% for appointment keeping. Hypertension plus obesity was the only factor significantly associated with noncompliance (OR 4.58, CI 95% 1.0, 22.4, p=0.02). CONCLUSIONS: The frequency of therapy noncompliance was very high, especially for diet and exercise.